HUBUNGAN CITRA MERK BUS (MGI) DENGAN KEPUASAN KONSUMEN PADA TRAYEK BANDUNG-SUKABUMI - Ulfa Chairunnisa (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2012)
This research aims to study correlation between brand image and customer satisfaction. Quantitative design using correlational method involved 350 MGI bus customer in Bandung-Sukabumi route. Instruments used are Brand Image Inventory (37 item) and Customer Satisfaction Index (37 item). Cooeficient correlation resulted is 0.684 which means that there is positive correlation between brand image and customer satisfction. High brand image correlated with high customer satisfaction while low brand image correlated with low customer satisfaction.